A review of papillary breast carcinoma in women attending a breast imaging centre in Johannesburg - Musawenkosi M. Mthombeni; Nasreen Mahomed; Grace Rubin; Sharadini K. Gounden (South African Journal of Radiology)
Background: Breast cancer ranks globally as the most prevalent cause of female deaths. Papillary breast carcinoma (PBC), a rare subtype of breast cancer, presents distinct challenges in diagnosis and management because of its unique histopathological features.